Selling the end of terrorism: a framing approach to the IRA's disengagement from armed violence. (3rd July 2016) - Clubb, Gordon
Abstract: Experiences from the end of the Provisional Irish Republican Army's campaign of armed violence have informed broader debates on how terrorism ends, yet this research has underplayed the internal dynamics which made the IRA's disengagement successful. The article utilises a framing approach to explain how a network within the IRA managed to ensure the majority of the movement supported an end to violence. A disengagement frame was constructed by this network within the IRA which maintained narrative fidelity, it utilised the credibility of mid-ranking commanders, and there were sufficient linkages to diffuse the frame due to generational hegemony, the structure of the IRA, and the unique structure of the prisons system. Finally, the article challenges the utility of decapitation strategies because organisational stability can maintain the components which ensure a disengagement frame will resonate.